Experimental and theoretical study of the behavior of hydrogen in rare earths - Marchetti, Jorge Mario (2005)
In this work, we study the behavior of hydrogen in some rare earths lanthanum (La), cerium (Ce), lutetium (Lu), and in two of its chemical precursors, scandium (Sc) and ytrium (Y). In the experimental aspect, samples of pure La were hydrided by direct contact with hydrochloric acid. In order to evaluate the influence of acid concentration on the hydriding, two different concentrations (12 and 1.2 M) were tested. The hydrogen content was measured by means of a LECO equipment and the hydriding fronts were observed by optical and scanning electronic microscopy. From the theoretical point of view, we determine some fundamental properties such as: screening charge density, volume of solution of hydrogen, heat of solution and variation of the density of states. Using a program based on the theory of the functional density, we model the material as an "effective jellium" (Phys. Rev. B 22 (1980) 1564).